2009
DOI: 10.1029/2009wr008320
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of the multirate basis for time convolution to unequal forward and reverse rates and connection to reactions with memory

Abstract: [1] The convolution form used to express mass transfer between mobile and immobile aqueous domains, and often associated with multirate mass transfer representations of matrix diffusion processes, is generalized to the case of unequal forward and reverse rates for each of the multiple rates of the multirate mass transfer and is shown to represent also linear but non-Markovian reactions that kinetically partition mass between mobile and immobile phases with rate of return to mobile phase dependent on contiguous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…[], as shown in Dentz and Berkowitz [], who point out that both models can be cast in the same integrodifferential equation form. Furthermore, Ginn [] showed a modified form of the MRMT can be cast in the form of the exposure time model of Ginn []. In summary, all three of these approaches are different ways of accommodating a multiplicity of reentrainment rates of colloids.…”
Section: Existing Upscaling Under Unfavorable Conditions: Two‐region mentioning
confidence: 99%
See 1 more Smart Citation
“…[], as shown in Dentz and Berkowitz [], who point out that both models can be cast in the same integrodifferential equation form. Furthermore, Ginn [] showed a modified form of the MRMT can be cast in the form of the exposure time model of Ginn []. In summary, all three of these approaches are different ways of accommodating a multiplicity of reentrainment rates of colloids.…”
Section: Existing Upscaling Under Unfavorable Conditions: Two‐region mentioning
confidence: 99%
“…In fact, this factored form of the CTRW is mathematically equivalent to the well-known multirate mass transfer modeling (MRMT) approach of Haggerty et al [2000], as shown in Dentz and Berkowitz [2003], who point out that both models can be cast in the same integrodifferential equation form. Furthermore, Ginn [2009] showed a modified form of the MRMT can be cast in the form of the exposure time model of Ginn [2000aGinn [ , 2000b. In summary, all three of these approaches are different ways of accommodating a multiplicity of reentrainment rates of colloids.…”
Section: Power Law Tailingmentioning
confidence: 99%
“…Slow diffusion process allows intra-granular solutions to evolve close to mineral equilibrium that can deviate from that in bulk solutions. Geochemical reactions such as sorption/desorption (Ball and Roberts 1991;Qafoku et al 2005;Liu et al 2008;Ginn 2009) and mineral precipitation and dissolution (McGreavy et al 1992;Lee et al 1998;Anderson et al 2002;Liu et al 2006;McKinley et al 2006McKinley et al , 2007Pallud et al 2010a) can occur in defi ance of thermodynamic conditions in bulk solutions. The slow diffusion, on the other hand, decreases mass exchange rate with external pore waters, leading to non-ideal behavior of chemical transport even for non-reactive species (Beven and Germann 1982;Ball and Roberts 1991;Ewing et al 2010Ewing et al , 2012Hay et al 2011).…”
Section: Grain-scale Reactions Sub-grain Process Coupling and Effecmentioning
confidence: 98%
“…By introducing the exposure time as additional dimension, and considering that a sample is a weighted average over different exposure times, the author tried to explain inconsistencies of advective-dispersivereactive transport in the presence significant chemical heterogeneity. While the author has applied the approach as "generalized exposure-time" concept to various problems of transport (e.g., Ginn, 2009), it comes with the key disadvantage of increasing the computational effort from 3-D or 4-D spacetime to a 4-D or 5-D domain (see also the Laplace-transfrom technique to evaluate the exposure-time distribution developed by Cornaton, 2012). In the present study, we thus do not consider full exposure-time distributions at a single point in space and time, and restrict the analysis to the mean exposure time, which can be evaluated by a slightly modified version of the mean groundwater-age equation (Goode, 1996).…”
Section: Introductionmentioning
confidence: 99%